Periodontal Ligament Stem Cells: Regenerative Potency in Periodontium - Tomokiyo, Atsushi; Wada, Naohisa; Maeda, Hidefumi (Stem cells and development, 2019)
Periodontium is consisted of root cementum, bone lining the tooth socket, gingiva facing the tooth, and periodontal ligament (PDL). Its primary functions are support of the tooth and protection of tooth, nerve, and blood vessels from injury by mechanical loading. Severe periodontitis induces the destruction of periodontium and results in a significant cause of tooth loss among adults. Unfortunately, conventional therapies such as scaling and root planning are often only palliative. Therefore, the ultimate goal of the treatment for periodontitis is to restore disrupted periodontium to its original shape and function. Tissue engineering refers to the process of combining cells, scaffolds, and signaling molecules for the production of functional tissues to restore, maintain, and improve damaged organs. The discovery of periodontal ligament stem cells (PDLSCs) highlighted the possibility for development of tissue engineering technology-based therapeutics for disrupted periodontium. PDLSCs are a kind of somatic stem cells that show potential to differentiate into multiple cell types and undergo robust clonal self-renewal. Therefore, PDLSCs are considered a highly promising stem cell population for regenerative therapy in periodontium; however, their rarity prevents the progression of basic and clinical researches. In this review, we summarize recent research advancement and accumulated information regarding the self-renewal capacity, multipotency, and immunomodulatory effect of PDLSCs, as well as their contribution to repair and regeneration of periodontium and other tissues. We also discuss the possibility of PDLSCs for clinical application of regenerative medicine and provide an outline of the genetic approaches to overcome the issue about the rarity of PDLSCs.